Exercising Local-Wisdom-based Character Education in Madrasah: an Ethnographic Study in a Madrasah in Sambas, West Kalimantan - Purniadi Putra; Aslan Aslan (UIN Sunan Ampel Surabaya, 2019)
The influence of hedonistic culture has led to a character crisis in various societies in the archipelago. Local wisdom with plurality, tolerance, and mutual cooperation, seems to be the anti-thesis of a hedonistic life. From here, various thoughts emerge about the importance of fostering character education based on local wisdom in Islamic education institutions. With an ethnographic approach, this study explores the application of character building efforts in madrasas in Sambas which are based on local cultural elements. The results showed that the use of 'Teluk belanga' and kurung clothes contributed to the formation of Islamic behavior, social life, and respect for local culture.